Formulation of construction projects as single-mode resource-constrained project scheduling problems (SMRCPSP) - Adamu, P.; Abass, O.; Okafor, R. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2007)
The paper presents the resource–constrained project-scheduling problem with the single execution mode for each activity and makespan (project’s completion time) minimization as objective. Several heuristic procedures for solving the problem have been proposed in the literature including a decomposition-based genetic algorithm and maximizing the net present value of projects.The formulation of construction projects as SMRCPSP using the bill of quantities, material schedule and the program of the construction projects, using a building construction project is presented.  Applying any of the good existing algorithms for solving this class of problems, will enable civil engineers to determine how to schedule the jobs in a construction project for execution so that completion times are minimized even if resources are insufficient? This will help to reduce the rate at which individuals or construction companies abandon their projects half way to completion times. It is a viable way to manage resource crises in construction companies